PEMBERDAYAAN PETUGAS PEMADAM KEBAKARAN DALAM BANTUAN HIDUP DASAR PADA KASUS GAWAT DARURAT - rizani, khairir; Hammad, Hammad; Sri PN, Endang; Rachmadi, Agus; Rizani, Akhmad; Marwansyah, Marwansyah; Wilutono, Nasrullah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2022)
In conditions where accidents and various disasters occur in the community, the people often contacted by the community are the firefighters. Empowering firefighters on basic life support in this case becomes very important due to their important role in the community. Community service methods by providing guidance and simulations to firefighters in Banjar Regency. Community service results after being assessed by all firefighters in Banjar Regency can recognize signs of heart and lung emergency and can correctly simulate CPR assistance. Building the capacity of firefighters and other community groups in Banjar Regency to provide CPR assistance is very important given that Banjar Regency is a disaster prone area.   Keywords: empowerment, BHD, firefighter